2016
DOI: 10.1177/1077546314562877
|View full text |Cite
|
Sign up to set email alerts
|

Propagation of a torsional surface wave in a non-homogeneous anisotropic layer over a heterogeneous half-space

Abstract: This paper aims to study the dispersion of torsional surface waves in a non-homogeneous anisotropic layer over heterogeneous half-space. We consider the inhomogeneity varies exponentially with depth in the layer and in half-space three types of heterogeneities, namely, quadratic, hyperbolic and exponential are assumed. The dispersion equation has been deducted for each case in a closed form by means of variable separable method. It has been observed that for homogeneous isotropic upper layer over a homogeneous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Here, c ij denotes the speed of a plane wave moving along the x i -axis with displacement along the x j -axis. Using equation ( 12), we haveṠ 0pi = J A 0piqj D j,q (28) in space andṠ 0pi = J A 0piqj D j,q (29) in the layer. For i = 3, the boundary conditions arė…”
Section: Love Waves At the Boundary Of The Initially Stressed Compressible Half-space And Layermentioning
confidence: 99%
See 1 more Smart Citation
“…Here, c ij denotes the speed of a plane wave moving along the x i -axis with displacement along the x j -axis. Using equation ( 12), we haveṠ 0pi = J A 0piqj D j,q (28) in space andṠ 0pi = J A 0piqj D j,q (29) in the layer. For i = 3, the boundary conditions arė…”
Section: Love Waves At the Boundary Of The Initially Stressed Compressible Half-space And Layermentioning
confidence: 99%
“…The effect of the point source on the speed of Love waves in a homogeneous half-space and heterogeneous layer was studied in [27]. Wave propagation in an initially stressed anisotropic material and incompressible transversely isotropic elastic solid was developed in [28][29][30][31][32]. The outcome of initial stress on elastic materials is analyzed in [18,33,34], which found that the existence of initial stress exerts significant restrictions on strain energy.…”
Section: Introductionmentioning
confidence: 99%
“…Bleustein (1968) discussed surface wave propagation in piezoelectric plates. Kundu et al (2016) examined torsional surface waves propagating through an anisotropic layer overlying a semi-infinite medium. SH-wave propagation through a solid medium reviewed by Wang (2002) was separated from the vacuum by a piezoelectric material layer.…”
Section: Introductionmentioning
confidence: 99%
“…This information forces us to consider the quadratic (in the upper layer) and trigonometric (in the lower half-space) variations of heterogeneity in the considered layered model. Earlier, seismic waves propagation through inhomogeneous elastic media was studied by Wilson (1942) and many investigations were carried out on the propagation of surface waves in various media under the presence of heterogeneity as Anderson (1962), Birch (1952), Kundu et al (2016), Ke et al (2005) and Ke et al (2006).…”
Section: Introductionmentioning
confidence: 99%